Unlocking the profit potential of intercropping of vegetables in farming systems - Kashyap, Poonam; Prusty, A. K.; Ravisankar, N.; Chaudhary, Jairam; Meena, Amrit Lal; Jat, P. C.; Ansari, M. A. (Indian Farming, 2025)
Intercropping with vegetables is an agricultural practice that involves growing multiple crop species together in the same field, promoting biodiversity and optimizing resource use. This practice offers a variety of economic, environmental, and agronomic benefits, particularly in smallholder farming systems. By intercropping vegetables with staple crops or fruit orchards, farmers canenhance soil fertility, improve pest and disease control, increase overall crop yields, and diversify farm income. The integration of vegetables, with their shorter growth cycles and higher market demand, provides additional income streams for farmers, especially during the early stages of crop growth. Moreover, intercropping enhances the efficiency of water and nutrient usage, reduces soilerosion, and promotes better soil microbial ecosystem, leading to improved long-term soil health. Intercropping plays a vital role in improving food security, economic stability, and sustainability in farming, particularly in regions facing resource limitations and climate change challenges. The adoption of intercropping with vegetables can be a sustainable farming strategy, contributing to enhanced productivity, resilience and profitability.